Germination and field establishment of Indiangrass populations selected for greater laboratory seed germination in a simulated dry condition. Issue 6 (12th October 2022) - Springer, Tim; Moffet, Corey
Abstract: Rapid seed germination followed by rapid seedling establishment are important traits for field establishment of grasses under variable climatic conditions. This research was designed to improve the seed germination of three Indiangrass [ Sorghastrum nutans (L.) Nash] populations through two cycles of recurrent selection and to field test the nine populations. Two cycles of recurrent selection were used to develop C1 and C2 populations from three previously unselected populations of Indiangrass. Cycle 1 consisted of germinating 3, 500 open‐pollinated seeds of each C0 population in water of −0.8 MPa potential for 7 d. All germinated seeds within 7 d were selected to create three C1 populations. Cycle 2 selection was like Cycle 1, except that C1 populations were used to develop three C2 populations. To test the effects of selection, four 50‐spikelet samples of the nine Indiangrass populations were germinated in water of −0.8 and 0 MPa potentials for 7 d for two seed harvests. Both water potentials produced a population × selection generation interaction ( P ≤ .05). Different rates of gain among the Indiangrass populations for water potential treatments (−0.8 and 0 MPa) described the interactions. On average, C1 and C2 populations emerged and survived better than C0 populations in the field. Thus, the data suggest that recurrent selection for increased laboratory seed germination of Indiangrass in a low water potential not only improved the 7‐d laboratory seed germination, but seed mass and stand establishment as well. Core Ideas: Rapid seed germination and seedling development is important for native grass establishment. Selecting Indiangrass for germination at low water potential improved germination and spikelet mass. Indiangrass field establishment was enhanced by selection for germination at low water potential.